2020
DOI: 10.1002/anie.202008866
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Pd‐Catalyzed Direct Coupling of Aryl Chlorides with Alkyllithium Reagents

Abstract: Organolithium compounds are amongst the most important organometallic reagents and frequently used in difficult metallation reactions.H owever,t heir direct use in the formation of C À Cbonds is less established. Although remarkable advances in the coupling of aryllithium compounds have been achieved, Csp 2 ÀCsp 3 coupling reactions are very limited. Herein, we report the first general protocol for the coupling or aryl chlorides with alkyllithium reagents.P alladium catalysts based on ylide-substituted phosphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 70 publications
(20 reference statements)
0
31
0
1
Order By: Relevance
“…10 ). 66 The donor strength and the steric properties of the YPhos ligands were found to be highly tunable depending on the nature of the Z substituent in the ylide-backbone. Thus, while offering steric protection through the large phosphonium moiety, donor strengths similar to those of NHCs, which are usually considered to be stronger donors, could be reached.…”
Section: Ylide-stabilized Group 15 Compoundsmentioning
confidence: 99%
“…10 ). 66 The donor strength and the steric properties of the YPhos ligands were found to be highly tunable depending on the nature of the Z substituent in the ylide-backbone. Thus, while offering steric protection through the large phosphonium moiety, donor strengths similar to those of NHCs, which are usually considered to be stronger donors, could be reached.…”
Section: Ylide-stabilized Group 15 Compoundsmentioning
confidence: 99%
“…[19,42] During research on ylide and yldiide compounds as ligands in transition metal complexes and the stabilization of reactive low-valent main group elements, Gessner and co-workers connected the strongly π-donating ylidyl groups as substituents to a phosphorus atom and obtained electron-abundant ylidylphosphines (YPhos). [108,109,110,111,112] Three simple reaction paths A-C in Scheme 14 were presented to synthesize ylidylphosphines starting from alkylphosphonium salts, which can be easily prepared via reaction of the respective phosphine with alkylhalides (Scheme 14). [113,115] Depending on the nature of Z, double deprotonation with metal bases and subsequent nucleophilic substitution at halophosphines deliver the desired YPhos ligands 34a-e in moderate to high yields of 69-92 % (route A).…”
Section: Ylidylphosphinesmentioning
confidence: 99%
“…[106] The latest findings in palladium catalysis gave rise to rather labile PÀ C bonds of triphenylphosphonium functionalities in common YPhos ligands, which results in inactive catalytic systems on course of the reaction, Gessner et al replaced the phenyl by cyclohexyl groups. [108,109,114] The resulting ligands in Cy Y Me PCy 2 (34k-m) show elevated stability and a remarkable performance in palladium-catalyzed amination reactions of aryl chlorides at room temperature (Scheme 14). [108,109] YPhos ligands in general represent valuable electron-rich phosphines, which was demonstrated by their readily formation of transition metal complexes, such as gold(I) [106,111,115] or palladium [112][113][114] complexes, which have been successfully employed as catalysts in amination and hydroamination reactions, as well as alpha arylation with arylchlorides among others.…”
Section: Ylidylphosphinesmentioning
confidence: 99%
See 1 more Smart Citation
“…[3b,14] Here, especially amines and ethers play a vital role. [14c] Currently, organolithium chemistry is evolving in several directions: First, experimental charge density studies revealed the nature of these unusual coordination bonds, [15] second, catalytic coupling reactions are still improved, [16] third, greener approaches try to avoid the usage of solvents and exploit solid organolithium compounds in mechanochemical reactions, [17] and fourth, they might be applied for syn-gas chemistry. [18] Besides the crystallographic studies, which give the exact structure, but only of (single-)crystalline compounds, NMR spectroscopic studies reveal the aggregation in solution, which sometimes differs, depending on, e. g., concentration and solvent.…”
Section: Introductionmentioning
confidence: 99%